PERAN PIMPINAN PONDOK PESANTREN DALAM MEMBANGUN SANTRI YANG MEMILIKI KEFAKIHAN PADA AL-QUR’AN - Ahmad Jazuli; Pauzan Haryono (LPPM Universitas Islam 45, 2023)
This study aims to describe how the condition of the taqwa of students in the Al-Qur'an and what is the role of the pesantren leadership in developing the taqwa of students in the Al-Qur'an. This research is a field research with a qualitative approach using data collection techniques in the form of observation, documentation and interviews. The results of this study indicate that not all students have the same knowledge in the Qur'an, this is due to various educational backgrounds. these differences, the leadership of the QBS Islamic boarding school Raudhatul Irfan has arranged this by providing teaching and methods that make it easier for students to learn and develop devotion to the Qur'an. The method of building students' faith in the Qur'an is by using the Qiroati and Amtsilati methods.